2002
DOI: 10.1103/physrevb.65.224302
|View full text |Cite
|
Sign up to set email alerts
|

Crossover from ionic hopping to nearly constant loss in the fast ionic conductorLi0.18La0.61TiO

Abstract: Electrical conductivity measurements of the fast ionic conductor Li 0.18 La 0.61 TiO 3 have been conducted at temperatures ranging from 8 to 300 K and frequencies between 20 Hz and 5 MHz. A detailed analysis of the ac conductivity shows the existence of a crossover between two different regimes. At high temperatures and/or low frequencies correlated ion hopping is responsible for a power-law frequency dependent and thermally activated ac conductivity. On the other hand, at sufficiently low temperatures and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 37 publications
(31 reference statements)
3
22
0
1
Order By: Relevance
“…Disordered materials like ionically conducting glasses and polymers show this "stretched" exponential behavior in the electrical conductivity relaxation, showing the importance of ion-ion correlations in the ion hopping process. 18,19 The parameter n has been proposed to be close to 1 for strongly correlated ion motion and equals to 0 for completely random and independent Debye-like ion hops. 20 Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Disordered materials like ionically conducting glasses and polymers show this "stretched" exponential behavior in the electrical conductivity relaxation, showing the importance of ion-ion correlations in the ion hopping process. 18,19 The parameter n has been proposed to be close to 1 for strongly correlated ion motion and equals to 0 for completely random and independent Debye-like ion hops. 20 Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The question considered in Section 2.3, i.e., whether the hopping part and the NCL part are additive constituents to the total conductivity, was examined also in earlier works by Ngai et al [26][27][28]. Their formal ingredients for describing the two parts were different from ours and, as a consequence, the two components were found to be non-additive [28].…”
Section: Temperature Dependence Of An Ncl Effect In Glassmentioning
confidence: 88%
“…4,10 Based on this fact and on several other properties of the NCL experimentally observed in ionic conductors, Ngai proposed its physical origin might be due to the displacement of the mobile ions in their local vibrational motion at low temperature and/or high frequency. León et al [11][12][13] later found experimental evidence, in two different lithium ionic conductors, consistent with such an origin for the NCL contribution to the ac conductivity. From the measurement of the crossover temperature ͑frequency͒ at which the NCL behavior terminates at different fixed frequencies ͑temperatures͒, they were able to determine an activation energy E NCL for the crossover which was found to be much lower than the activation energy E dc for the dc conductivity, governed by ion hopping dynamics, and in fact E NCL was found to be similar to the value estimated for the energy barrier for the ions to leave their cages, E a .…”
mentioning
confidence: 79%